ANALISIS GAP PEMAHAMAN PIMPINAN UNIT KERJA TERHADAP IMPLEMENTASI SISTEM MANAJEMEN MUTU (SMM) BERBASIS ISO 9001:2008 DI SMK NEGERI 1 KOTA TASIKMALAYA - , Maman; , Drs.Wakhid Slamet Ciptono,, MBA., MPM., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The PUK Understanding the Gap Analysis Implementation based on ISO 9001:2008 QMS in SMK Negeri 1 Kota Tasikmalaya, Thesis, Master of Management, University of Gadjah Mada, Yogyakarta. Efforts to improve the quality of service that heralded this time the Government is to provide service to customers with clear standards. SMK Negeri 1 Kota Tasikmalaya try to respond to efforts to improve the service by implementing ISO 9001:2008-based QMS. As a logical consequence, as Singh and Sareen (2006) conclude that further research is needed to fully assess the consequences of the application of ISO 9000 in educational institutions, This study was conducted to identify the 13 people PUK understanding the implementation of ISO 9001:2008 based QMS in SMK Negeri 1 Kota Tasikmalaya. PUK level of understanding in this study measured the quality of training and have certificates awareness, recognition of his work on understanding the instructions on each unit, the recognition of other PUK, and the documents that are the responsibility of the respective unit. PUK categorized understand, if it meets all four of these requirements, please understand if it meets two or three terms unless the terms of the documents. PUK categorized not understand, if the conditions are not met the complete document. The research method used is descriptive method to analyze the results of interviews, checklists, primary data and secondary data contained in SMK Negeri 1 Kota Tasikmalaya. Data were then analyzed qualitatively, which includes data reduction, data display and conclusion. The results showed 13 people PUK uncategorized 4 people understand, 6 people and 3 people know enough not understand. This shows the gap of understanding that could potentially hinder the implementation of QMS based on ISO 9001:2008. Improved understanding of the PUK taken the school through: 1). Awareness training quality